Migrant labour, racism and the British national health service - Virdee, Satnam K.; Kyriakides, Christopher (My University, 2003)
This study explores the dynamics of racism, specifically its generation and reproduction as an ideology, and its role in affecting the reception and occupational location of migrant medical labour in Britain. It is argued that the treatment of 'overseas doctors' in Britain draws on a complex interplay between racism and nationalism underpinned by the historical construction of 'welfarism' as a moral legitimator of 'Britishness'. Through an exploration of internal and external immigration controls introduced with the aim of regulating migrant labour, we demonstrate how British social policy and elite discourses of 'race' combine to construct moral prescriptions of threat such that migrants and British-born 'non-whites' entering the British medical profession are forced to negotiate 'saviour/pariah' ascriptions indicative of discriminatory but contradictory processes specific to the operation of the British National Health Service as a normative institution.
Keywords: Racism; Articles; Emigration and immigration; Ideology